2008
DOI: 10.1093/hmg/ddn278
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of placental cholesterol transport: ABCA1 is a potential target for in utero therapy of Smith-Lemli-Opitz syndrome

Abstract: Patients with Smith-Lemli-Opitz syndrome (SLOS) are born with multiple congenital abnormalities. Postnatal cholesterol supplementation is provided; however, it cannot correct developmental malformations due to in utero cholesterol deficit. Increased transport of cholesterol from maternal to fetal circulation might attenuate congenital malformations. The cholesterol transporters Abca1, Abcg1, and Sr-b1 are present in placenta; however, their potential role in placental transport remains undetermined. In mice, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 55 publications
5
50
0
1
Order By: Relevance
“…Reduced fatty acid transport can also directly compromise placental function, owing to excess accumulation and subsequent oxidative stress (Jarvie et al, 2010). The high fetal demand for cholesterol in late gestation is met by both placental transfer from the maternal circulation and by fetal de novo synthesis (Lindegaard et al, 2008;Yoshida and Wada, 2005). Therefore, changes in placental cholesterol uptake and transfer are more likely to affect the fetal brain via further impact on placental function.…”
Section: Nutrient Exchange and Energy Homeostasismentioning
confidence: 99%
“…Reduced fatty acid transport can also directly compromise placental function, owing to excess accumulation and subsequent oxidative stress (Jarvie et al, 2010). The high fetal demand for cholesterol in late gestation is met by both placental transfer from the maternal circulation and by fetal de novo synthesis (Lindegaard et al, 2008;Yoshida and Wada, 2005). Therefore, changes in placental cholesterol uptake and transfer are more likely to affect the fetal brain via further impact on placental function.…”
Section: Nutrient Exchange and Energy Homeostasismentioning
confidence: 99%
“…41 In DHCR7 À/ À mice, it was shown that disruption of ABCA1 is associated with a 30% decrease of cholesterol transfer to the fetus, suggesting that ABCA1 plays a crucial role in placental cholesterol transfer. 42 In this setting, it is important that ABCA1 has no effective ATPase activity and therefore does not directly facilitate the transport of cholesterol from mother to child. Rather, it has a regulatory role in this process.…”
Section: Discussionmentioning
confidence: 99%
“…[180][181][182][183] Tissue that would otherwise have been discarded, including placentas and umbilical cords, can be obtained for research purposes because their collection poses little risk to the patients. [185][186][187] The placenta has been used in child-health research to investigate preeclampsia, 188 maternal obesity, 63 endocrine disruptors, 189 attention-deficit/hyperactivity disorder, 64 Smith-Lemli-Opitz syndrome, 190 and vertical virus transmissions. 65,66 Blood drawn from umbilical cord veins has been used for regenerative medicine 72 and stem cell research.…”
Section: Sources and Types Of Solid Tissues Collectedmentioning
confidence: 99%